Legal Protection of Investors in Investment Activities to Support Development in Indonesia - Mufidah, Nabilah (Ipso Jure, 2024)
Achievements in the economic field can be done in several ways, one of which is investment. Developments in investment are one of the factors in Indonesia's economic growth. Economic growth can support development in Indonesia. For the right investment to occur, it can affect the welfare of the people in Indonesia. Legal protection aims to protect the public from all arbitrary actions that can violate the rule of law. The purpose of legal protection is to create order and peace in society